Framing a new reality: documenting genocide in District 9. Issue 4 (20th October 2017) - Conway, Daniel
ABSTRACT: In his 2009 film District 9, Neill Blomkamp employs a handheld camera to create the effect of an embedded documentary film, which ostensibly is devoted to an objective treatment of the escalating tensions between a stranded alien race – known only (and derogatorily) as the 'Prawns' – and the increasingly agitated citizens of Johannesburg. Mobilizing the self-critical perspective afforded him by this mise en abyme, Blomkamp demonstrates the extent to which the presumption of objectivity allows the documentary filmmaker to frame the new reality to which a reluctant populace gradually accustoms itself. As depicted in the embedded documentary, the new reality is that human–Prawn relations have been damaged beyond repair. As such, the proposed relocation of the Prawns, which initially may have been utterly unthinkable to most residents of Johannesburg, rounds into view as the best and most reasonable option for all involved. According to Blomkamp, that is, the anonymous documentarians not only report the slow, incremental embrace of genocide – represented in the film by the unseen District 10 – but also play a largely unacknowledged role in promoting this transition.